Tests of articulation in Kannada - P, Rama Mohan Babu; N, Rathna; Ramesh Bettageri (Journal of All India Institute of Speech and Hearing, 1972)
Uptil now no articulation tests, standardized or otherwise, are available in Kannada. Articulation tests such as that of Templin-Darley’s and Milisen’s are available in English, but they cannot be used with people who speak languages other than English. There is a dire necessity of standardized articulation tests in all languages as shown by the results of the following study. A nation-wide survey of Public School Speech Clinicians in U.S. conducted by W. Johnson et al., in 1952 showed that 90.5 per cent of the total case load have articulation problems. So we are presenting two procedures for describing and assessing an individual’s articulation patterns.